2020
DOI: 10.1051/0004-6361/201936924
|View full text |Cite
|
Sign up to set email alerts
|

Correcting the effect of magnetic tongues on the tilt angle of bipolar active regions

Abstract: Context. The magnetic polarities of bipolar active regions (ARs) exhibit elongations in line-of-sight magnetograms during their emergence. These elongations are referred to as magnetic tongues and attributed to the presence of twist in the emerging magnetic flux-ropes (FRs) that form ARs. Aims. The presence of magnetic tongues affects the measurement of any AR characteristic that depends on its magnetic flux distribution. The AR tilt-angle is one of them. We aim to develop a method to isolate and remove the fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The magnetic tongues, or elongations of two main polarities of an active regions during their emergence were first reported by López Fuentes et al (2000). Poisson et al (2020) have shown that the active regions with weaker magnetic tongues show the magnetic tilts similar to those derived from white light images. However, for active regions with strong magnetic tongues, there could be significant difference in tilts derived from white light images and magnetograms.…”
Section: East-west Orientation Of Active Regionssupporting
confidence: 51%
See 2 more Smart Citations
“…The magnetic tongues, or elongations of two main polarities of an active regions during their emergence were first reported by López Fuentes et al (2000). Poisson et al (2020) have shown that the active regions with weaker magnetic tongues show the magnetic tilts similar to those derived from white light images. However, for active regions with strong magnetic tongues, there could be significant difference in tilts derived from white light images and magnetograms.…”
Section: East-west Orientation Of Active Regionssupporting
confidence: 51%
“…For example, larger tilts will enhance the poleward transport of the magnetic flux of trailing polarity, and depending on the polarity orientation, could either strengthen or weaken the polar field (e.g., Baumann et al, 2004;Whitbread et al, 2017;Petrovay and Talafha, 2019). Several studies of the Hale polarity rule and the tilt angle of active regions were published in recent years (Illarionov et al, 2015;Li, 2018;Tlatova et al, 2018;Kuzanyan et al, 2019;Kleeorin et al, 2020;Poisson et al, 2020). Thus, for example, Poisson et al (2020) emphasized the importance of, so called, magnetic tongues in the determination of active region tilts using longitudinal magnetograms.…”
Section: East-west Orientation Of Active Regionsmentioning
confidence: 99%
See 1 more Smart Citation